Experiences of empathy training in healthcare: A systematic review of qualitative studies - Rachel Winter; Navin Leanage; Nia Roberts; Robert I. Norman; Jeremy Howick (2022)
To synthesise qualitative studies reporting student, practitioner, or patient experiences of empathy-training in healthcare.We included qualitative studies exploring (i) student or practitioner experiences of empathy training, or (ii) patient experiences of being treated by someone who has undergone empathy training. We used the Critical Appraisal Skills Programme (CASP) tool to assess study quality. Thematic synthesis was used to integrate findings from studies and to generate new insights.Our search yielded 2768 citations, of which 23 (1487 participants) met inclusion criteria. Two clusters of themes were identified from included studies. Firstly, themes related to practitioner/trainee professionalism and wellbeing, where the main finding was that participants experienced benefit from therapeutic empathy training. Secondly, themes related to the understanding and treatment of patients, where the main finding was practitioners' deeper recognition of the positive impact of empathic care.This review found that taking part in empathy-focused training can benefit practitioner/student personal growth and professional development, and benefits patient care. This review is limited by the difficulty in defining empathy and heterogeneity amongst included studies.These results support a rationale for empathy training and the development of a framework to ensure training is having the desired effect.